(untitled) (Neo Science Peer Reviewed Journal, 2023)
In the article, identifying ways to improve the effectiveness of machine learning algorithms for brain magnetic images, the article on the symptoms and diagnosis of stroke focuses on a comprehensive review of various aspects of stroke diagnosis, including its symptoms, diagnostic tools, and the difficulties in differentiating stroke from other conditions.